2011
DOI: 10.1186/1742-2094-8-83
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of rat piriform cortex following exposure to the organophosphonate anticholinesterase sarin and induction of seizures

Abstract: BackgroundOrganophosphorus nerve agents irreversibly inhibit acetylcholinesterase, causing a toxic buildup of acetylcholine at muscarinic and nicotinic receptors. Current medical countermeasures to nerve agent intoxication increase survival if administered within a short period of time following exposure but may not fully prevent neurological damage. Therefore, there is a need to discover drug treatments that are effective when administered after the onset of seizures and secondary responses that lead to brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…1a). The extensive activation of inflammatory responses in the seizing rats, in particular by neurotoxic and pro-inflammatory cytokines, such as Il-1β, Tnf-α, and Il-6, was observed in all brain regions (Spradling et al, 2011a(Spradling et al, , 2011b, consistent with findings from previous studies (Chapman et al, 2006;Dhote et al, 2007;Dillman et al, 2009;Johnson and Kan, 2010;Svensson et al, 2001Svensson et al, , 2005Williams et al, 2003).…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…1a). The extensive activation of inflammatory responses in the seizing rats, in particular by neurotoxic and pro-inflammatory cytokines, such as Il-1β, Tnf-α, and Il-6, was observed in all brain regions (Spradling et al, 2011a(Spradling et al, , 2011b, consistent with findings from previous studies (Chapman et al, 2006;Dhote et al, 2007;Dillman et al, 2009;Johnson and Kan, 2010;Svensson et al, 2001Svensson et al, , 2005Williams et al, 2003).…”
Section: Introductionsupporting
confidence: 91%
“…We determined the differentially expressed genes (DEGs) from the data of Spradling et al (2011b), using a false discovery rate (FDR)-corrected p-value cutoff of 0.05 for each of the five studied brain regions (amygdala, hippocampus, piriform cortex, septum, and thalamus) and at each time point (0.25 h, 1 h, 3 h, 6 h, and 24 h). The determination of the DEGs from each cohort of seizing and non-seizing rats employed separate control groups due to differences in countermeasure administration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High arsenic levels in drinking water (>100μg/L) increased the risk of peripheral artery disease, coronary heart disease, stroke, and carotid atherosclerosis in studies conducted in Chile, 177 Taiwan, 178 Inner Mongolia, 179,180 Bangladesh, 181,182 and Pakistan. 183,184 The prospective cohort study from Bangladesh also examined the lower threshold of arsenic concentrations of arsenic in water and found that concentrations above 12 μg/L were associated with an increased hazard of CVD mortality.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%